Obisk Mihaila Gorbačova v Jugoslaviji marca 1988 in jugoslovansko-sovjetska deklaracij - Bajc, Gorazd (Prispevki za novejšo zgodovino, 2020)
Based on the analysis of the archival materials from several Western countries, the press from that period, and the most relevant scientific literature, the article focuses on the visit of the General Secretary of the Central Committee of the Communist Party of the Soviet Union Mikhail Gorbachev to Yugoslavia in March 1988. In this regard, the circumstances of this visit to Yugoslavia, its course, and importance for the developments in Europe and worldwide as well as its assessments by the selected Western Bloc countries are analysed. The authors highlighted two aspects of the visit in particular. The first aspect is Gorbachev's visit that also included Slovenia, where he met with the leaders of the republic; and the second is the adoption and signing of the Yugoslav-Soviet Declaration that redefined the relations between the two states while simultaneously raising the question of whether its formulation represented the beginning of the end of the Brezhnev Doctrine.
Keywords: Brezhnev Doctrine; Brežnjeva doktrina; end of the Cold War; Gorbachev, Mihkail; Gorbačov, Mihail; Jugoslavija; konec hladne vojne; Soviet Union; Sovjetska zveza; Yogoslavija